Pemberdayaan Masyarakat Melalui Sosialisasi Lingkungan, Penanaman Pohon dan Pembagian Bibit serta Pembuatan Ecobrick di SDN 001 Buantan Lestari - Nurrahmi, Nurrahmi; Pratama, Surya; Natasia, Fiola; H, Aulya Indah Agustin (Universitas Nusantara PGRI Kediri, 2025)
Buantan Lestari Village is one of ten villages in Bunga Raya District, Siak Regency, Riau Province, Indonesia. Population density is positively correlated with the rate of household waste production. Topographically, the area of ​​Buantan Lestari Village is a lowland crossed by the Buantan River and has a fairly wide expanse of land with an altitude of around 5-17 meters above sea level. With this influence, greening and good waste management are needed. However, Buantan Lestari Village must face problems in this regard in the form of minimal awareness of knowledge and skills in planting and processing household waste. The implementation of this activity was carried out to help Buantan Lestari Village face this problem with a socialization method related to planting and managing household waste. With the implementation of this activity, the results of increased literacy regarding environmental awareness of greening and household waste management of participants with sustainability were obtained.